O imposto de renda e os resultados de pessoa jurídica domiciliada no Brasil auferidos através de filial localizada no exterior - Sprangim, Verônica (2007)
The objective of this work is to systematize the rules concerning the income tax imposed on the earnings of a legal entity domiciled in Brazil derived from a branch based overseas. To begin with an analysis was made of the rules present in the Federal Constitution, in order to identify the minimum content of the income concept and verification of the compatibility between the Constitution and the pertinent rules contained in the Brazilian Tax Code ( Código Tributário Nacional ). With reference to the structural rule of corporate income tax, we analyzed the calculation basis of the tax, examining at greater depth the negative elements in its composition. Given the need of fixing the content of the vocabulum used in the Federal Constitution for the identification of the elements of the income tax levy event, we resumed the question of the limits imposed on the statutory legislator in the exercise of his taxing power upon producing the institutor laws of this tax, especially in relation to the income , profit , assets and liabilities and legal entity concepts. We verified the existing relationship between the taxpayer and the fact described in the structural rule of income tax on the profits of legal entities, in an effort to identify the limits in the election of the debtor and the corresponding effect on the calculation basis, specifically, in the cases wherein it, the legal entity, applies the material criterion: earn income . We address the case of a legal entity owner of several establishments and the respective legal implication for the purposes of income tax. Finally, always through the application of a systematic method of interpretation, we study the rules that discipline the income earned by a legal entity domiciled in Brazil through a branch based overseas